2017
DOI: 10.4103/0973-1482.181177
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer presenting as bone metastasis

Abstract: Ten such patients were identified (male:female = 7:3) of the total 410 patients. Median age was 41 years (22-50 years). All patients were Conclusions: In this study, the patients of colorectal cancer presenting with bone metastasis were of male sex and younger age. The factors that were associated with reduced survival were extraosseous and liver involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…A retrospective study with 10 patients with CRC presented as bone metastases reported by Babu et al [ 4 ], tried to rule out some common features among those cases, but only in three of them the bone metastases were solitary. They detected that the most affected bones were vertebras and pelvis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A retrospective study with 10 patients with CRC presented as bone metastases reported by Babu et al [ 4 ], tried to rule out some common features among those cases, but only in three of them the bone metastases were solitary. They detected that the most affected bones were vertebras and pelvis.…”
Section: Discussionmentioning
confidence: 99%
“…It is historically recognized that CRC has a determined pattern of dissemination. The liver is the most affected organ in 60% of the cases, followed by abdominal lymph nodes and lungs [ 4 ]. In contrast, metastases in other organs such as adrenals, brain, bones or skin, are less frequent and commonly occur in the context of a widespread disease with multifocal affection, or a relapse after a primary treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, gender and age are among the factors related to poor survival, Babu et al presented a clinical study in which CRC patients with bone metastases were male and young. However, whether sex affects the prognosis of these subjects needs to be deeply investigated [17].…”
Section: Crc and Bone Metastasesmentioning
confidence: 99%